Sabertooths and the ice age a nonfiction companion to Magic tree house #7 Sunset of the sabertooth - Osborne, Mary Pope; Boyce, Natalie Pope Murdocca, Sal (Random House New York, 2011)
What was it like to live in the Ice Age and why was the world so cold? Who made the first cave paintings? What ever happened to sabertooth cats and wooly mammoths? Find out the answers to these questions and more in Magic Tree House Research Guide: Sabertooths and the Ice Age, Jack and Annie's guide to unlocking the mysteries of the Ice Age! This is the nonfiction companion to Sunset of the Sabertooth. A great place to begin research for a report